Konsep Diri Anak Jalanan - Nasti, Sarila Hasti Hadi; , Dr. Moordiningsih, M.Si, Psi (2016)
This research has purpose to determine the self-concept owned street children and the process of formation of self-concept of street children. This research used a qualitative approach, data collection using interviews and observation techniques. Informants in this study were selected seraca purposive sampling technique is snowball sampling. The informants were 10 people. The datas analysis is thematic. The results of this research found that street children have a negative self-concept. This can be seen from the aspect of self-assessment that is pessimistic, envy, failure, embarrassment with the appearance and feel of the body is not well maintained. Aspects of social judgment, which was worthless person, have no manners, shamefully, do not trust others, judged negatively of others, judged to be good, to discredit the family name. Street children accept the judgment of others against him, but sometimes street children will hit those who insult him if thats outrageous. Aspects of the self-image that street children have an ideal unrealistic, feel a lot of shortcomings, stupid, has a low IQ, parental shortcomings, embarrassed by the state of the parents and not be loved and cared for the elderly. Factors affecting the formation of self-concept of street children is a family, social support, socioeconomic status and a reference group. The concept of self-owned street children will influence the attitudes and behavior towards interpersonal relationships.